Three new species of the salamander genus Hynobius (Amphibia, Urodela, Hynobiidae) from Kyushu, Japan - Nishikawa, Kanto; Matsui, Masafumi (Zootaxa, 2014)
Three new species of lotic breeding Hynobius, formerly assigned to H. boulengeri, are described from the Kyushu region, southwestern Japan. They differ from all the known congeners by a unique combination of body size, character ratios, coloration, mtDNA, and allozymic characteristics. Together with H. stejnegeri they form a clade, which is not a sister group of H. boulengeri, and their speciation in Kyushu is surmised to have occurred at the end of Miocene, accompanied by differentiations in larval period and metamorphosing size. Measures of conservation of these new species are discussed briefly.